How to calculate the diameter, radius and circumference with circle area

How to calculate the diameter, radius and circumference with circle area


S = 3.14r & # 178;
For example
Area 314, instead of formula
3.14r²=314
r²=314÷3.14
r²=100
R = root sign 100 (originally = positive and negative root sign 100, but the radius cannot be negative, so it is: root sign 100)
r=10
I know the radius. The diameter will change!
Diameter = 10 × 2 = 20



Calculate the radius, diameter and area of the round flower bed according to the perimeter
Perimeter is 62.8 meters, radius, diameter and area


Radius 62.8 △ 3.14 △ 2 = 10m
Diameter 62.8 △ 3.14 = 20m
Area: 3.14 × 10 × 10 = 314 square meters



C + + design a circle class, calculate the area and perimeter of the circle
1. Define a circle, its attributes are radins, circumference and area, and its operation is input radius and calculate circumference, area, output radius and area. It is required to define constructor (with radius as parameter, default value is 0, perimeter and area are generated in constructor) and copy constructor
2. Define a point class, derive a rectangle class and a circle class, and calculate the area of objects of each derived class
3. There is a vehicle class vehicle, which is used as the base class to derive car class, truck class and boat class. Define these classes and define a virtual function to display all kinds of information


1.
class Circle
{
public:
Circle():r(0), leng(0), area(0){
}
Circle(const int rm):r(rm){
leng = 2 * pi * rm;
area = pi * rm * rm;
}
Circle& Circle(Circle& other){
r = other.r;
leng = other.leng ;
area = other.area ;
return *this;
}
void setR(const double rm)
{
r = rm;
leng = 2 * pi * r;
area = pi * r * r;
}
void output()
{
cout



If the quadratic trinomial x2-ax + 2a-3 about X is a complete square, then the value of a is ()
A. - 2b. - 4C. - 6D. 2 or 6


According to the meaning of the question: A2-4 (2a-3) = 0, the solution: a = 2 or 6



Try to explain: a (a + 1) (a + 2) (a + 3) is a complete square formula


Make sure the title is right?
It seems that a (a + 1) (a + 2) (a + 3) + 1 is a complete square
First, expand the formula
a(a+3)=a^2+3a
(a+1)(a+2)=a^2+3a+2
So the original formula = (a ^ 2 + 3a) (a ^ 2 + 3A + 2) + 1
Let x = a ^ 2 + 3A + 1
Original formula = (x-1) (x + 1) + 1
=x^2-1+1
=x^2
Original formula = (a ^ 2 + 3A + 1) ^ 2
So a (a + 1) (a + 2) (a + 3) + 1 is a complete square



Factorization 4m ^ 2 - (M + n) ^ 2
Tonight!


4m^2-(m+n)^2
=(2m+m+n)(2m-m-n)
=(3m+n)(m-n)



Factorization of 4m ^ 2 - (M + n) ^ 2


4m²-(m+n)²
=[(2m)+(m+n)][(2m)-(m+n)]
=(3m+n)(m-n)



Decomposition factor m ^ 2 + 2m-6n-9n ^ 2=


m^2+2m-6n-9n^2
=m^2-9n^2+2m-6n
=(m+3n)(m-3n)+2(m-3n)
=(m-3n)(m+3n+2)



Decomposition factor M & # 178; n-5mn + 6N


m²n-5mn+6n
=n(m²-5m+6)
=n(m-2)(m-3)
remarks:
cross multiplication
m²-5m+6
m -2
m -3
M * (- 3) + (- 2) * m = - 5m satisfies the first term



If the power of [M + 2] and (n-4) are opposite to each other, then the power of (- M) n is


m+2=-(n-4)*(n-4)
Because (n-4) (n-4) ≥ 0
So - (M + 2) ≤ 0
n-4=0 m+2=0
n=4 m=-2
(-m)^n=2^4=16